HETEROSIS AND GENE ACTION FOR YIELD AND YIELD COMPONENTS AND Maize (Zea mays L.), USING HALF DIALLEL CROSSES. - Shapal hasan Ramadan; A. T. Mohammed A. Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Experiment of half diallel cross among eight maize inbred lines was carried out during spring 2021.The varietal traits for F1 cross and parents with local hybrid were conducted during autumn 2021 Field of College of Agricultural Engineering Sciences , University of Duhok, using Randomized Complete Block Design with three replications .The results were revealed that the analysis of variance for genotypes and general and specific combining ability were significant effect on studied traits , also the ratio of degree of dominance is less then one for all traits . The cross 7x8 gave the heighest value ( 219.35g) for grain yield per plant and the same cross gave positive significant heterosis over mid parent , best parent and local hybrid .The heritability were high for number of ear per plant and ear diameter with value( 0.55) and( 0.45) respectively, the expected genetic advance was low for yield and yield components.